Multimodality and multiterritory vascular imaging in a toddler with acquired, complex, and unusual aortic arch anatomy. Issue 10 (6th September 2019) - Bhat, Aarti H.; Trent, Erin; Kapur, Raj P.; Permut, Lester
Abstract: A 20‐month‐old otherwise well child with no cardiac history presented for evaluation of a recent onset cardiac murmur. His initial examination revealed significant right carotid bruit along with a transthoracic echocardiogram (ECHO) concerning for severe transverse arch hypoplasia with unusual appearance and left ventricular hypertrophy with preserved function. This report demonstrates the utility of various modalities including echo, CT, and MRI to assess vascular structures in different vascular territories in a challenging patient who underwent a satisfactory arch repair with unexpected pathology findings.